A Novel Fibrinogen-clotting Enzyme, TL-BJ, from the Venom of the Snake Bothrops jararaca: Purification and Characterization - Serrano, Solange M. T.; Sampaio, Claudio A. M.; Mentele, Reinhard; Camargo, Antonio C. M.; Fink, Edwin (Thrombosis and Haemostasis, 2000)
Three chromatographically distinct forms of a novel fibrinogenclotting serine endopeptidase, TL-BJ 1, 2 and 3, were purified from the venom of Bothrops jararaca by a combination of ammonium sulfate precipitation and chromatographic steps. The three forms of TL-BJ have similar amidolytic and plasma coagulating activities. TL-BJ 1, TL-BJ 2 and TL-BJ 3 cause the specific clotting of fibrinogen with release of fibrinopeptide A, the specific activities are 16.8 NIH U/mg (TL-BJ 1), 16.7 NIH U/mg (TL-BJ 2) and 20.8 NIH U/mg (TL-BJ 3). The most sensitive chromogenic substrates for measuring the amidolytic activity of TL-BJ 3 were D-Pro-Phe-Arg-pNA, D-Phe-pipecolyl-ArgpNA and Z-D-Arg-Gly-Arg-pNA. The amidolytic and coagulant activities of TL-BJ were inhibited by phenylmethylsulfonyl fluoride but not by hirudin. Benzamidine derivatives, which are competitive inhibitors of trypsin-like serine endopeptidases, also inhibited the amidolytic activity of TL-BJ. In SDS/PAGE the main bands of TL-BJ 1, 2 and 3 showed molecular masses of 30 kDa, 31 kDa and 32 kDa. Upon incubation with N-glycosidase F only TL-BJ 3 remained unchanged, whereas TL-BJ 1 and TL-BJ 2 showed products with molecular masses around 23 kDa. Thus, TL-BJ 3 does not seem to be N-glycosylated. The N-terminal amino acid sequences of TL-BJ 2 and TL-BJ 3 are identical while TL-BJ 1 has five substitutions.
Keywords: Snake venom; purification; serine peptidase; fibrinogen-clotting